The Role of State Administrative Law in e-KTP Corruption Cases in Indonesia - Jardhan, Rheno; Sinaga, Ryanson Donovan; Batu, Jeremy Santos Lumban; Putra, Moody Rizqy Syailendra (CV. Rayyan Dwi Bharata, 2024)
The e-KTP corruption case highlights significant weaknesses in the implementation of administrative law in Indonesia, particularly in public procurement. Administrative law, which should regulate government actions and ensure transparency and accountability, failed to prevent corruption involving high-ranking officials, legislators, and business entities. This study examines the role of administrative law in handling the e-KTP corruption case and identifies the weaknesses within the administrative law system that allowed abuses of power to occur. Findings show that a lack of transparency, weak oversight, and minimal accountability were the main factors contributing to corruption in the e-KTP project. Therefore, reforms in the administrative law system are essential to improve governance towards greater transparency and efficiency.